g(-2) + g(2) = 22
Step-by-step explanation:
For x = -2, g(x) = x^2 - 3x
or
g(-2) = (-2)^2 - 3(-2) = 4 + 6 = 10
For x = 2, g(x) = 12, therefore
g(-2) + g(2) = 10 + 12 = 22
Answer:
4k(k-3)(2k-1)
Step-by-step explanation:
Answer:
0
Step-by-step explanation:
-20.5 is the same as -20.5
, since anything to the zero power is equal to 1.
Answer:
C
Step-by-step explanation:
Supplementary angles because their sum is 180 degrees
Answer:
i believe your answer is $7,200
Step-by-step explanation:
take 180 and divide it by .025, you should get $7,200.